2002
DOI: 10.1121/1.1430687
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of flow and energy fields near a thermoacoustic couple

Abstract: The flow field and the energy transport near thermoacoustic couples are simulated using a 2D full Navier-Stokes solver. The thermoacoustic couple plate is maintained at a constant temperature; plate lengths, which are ''short'' and ''long'' compared with the particle displacement lengths of the acoustic standing waves, are tested. Also investigated are the effects of plate spacing and the amplitude of the standing wave. Results are examined in the form of energy vectors, particle paths, and overall entropy gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 13 publications
(8 reference statements)
8
56
0
Order By: Relevance
“…The cited thermo-fluid processes occurring in stack ends are beyond the scope of the standard linear theory [19,21] because it's based on the uniform transverse time-average temperature [17]. Moreover, the experimental observations are retrieved by numerical investigations [5,8,17]. It confirms that the net heat exchange between fluid and wall takes place at distance from the stack ends not exceeding the peak to peak particle displacement.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The cited thermo-fluid processes occurring in stack ends are beyond the scope of the standard linear theory [19,21] because it's based on the uniform transverse time-average temperature [17]. Moreover, the experimental observations are retrieved by numerical investigations [5,8,17]. It confirms that the net heat exchange between fluid and wall takes place at distance from the stack ends not exceeding the peak to peak particle displacement.…”
Section: Introductionsupporting
confidence: 57%
“…In fact, more adequate computational fluid dynamic methods are used to solve unsteady compressible Navier-Stokes equations or the low Mach equivalent equations [3,5,8,10,11,24]. Alternatively, simpler methods are also used and are in good agreement with experiments [12,17].…”
Section: Introductionmentioning
confidence: 97%
“…Hence, for the heat exchanger types A and B, the obtained magnitudes have orders of B1 > B2 > B3 and A1 > A2 > A3. Numerical simulation by Ishikawa et al [21] showed that the net heat From the response surfaces with fixed various parameters, it is noted that l/d h , as a geometrical parameter, has a negative influence on the Nusselt number. The rise of l/d h leads to a dramatic weakening in the heat transfer performance.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, for the heat exchanger types A and B, the obtained magnitudes have orders of B1 > B2 > B3 and A1 > A2 > A3. Numerical simulation by Ishikawa et al [21] showed that the net heat transfer rate between solid and fluid states mainly occurred on the inlet and outlet faces of the heat exchanger with parallel plates. When the fin length is increased, the heat flux on inlet and outlet faces can be positive or negative, leading to a decrease in the net heat flux.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation